Continuation of the Pocahontas paradox: stereotypes of Aboriginal women presented in Halloween costumes - O'Dell, Keestin (My University, 2016)
The present study examined adult women’s Halloween costumes to see how Aboriginal women are presented through these costumes. Three types of Aboriginal women were identified in these costumes: the sexual native, the noble native and the rebellious native. Implications of these findings are discussed herein.
Keywords: Aboriginal women; stereotypes